3D sound source localization based on coherence-adjusted monopole dictionary and modified convex clustering. (October 2018) - Tachikawa, Tomoya; Yatabe, Kohei; Oikawa, Yasuhiro
Abstract: In this paper, a sound source localization method for simultaneously estimating both direction-of-arrival (DOA) and distance from the microphone array is proposed. For estimating distance, the off-grid problem must be overcome because the range of distance to be considered is quite broad and even not bounded. The proposed method estimates the positions based on a modified version of the convex clustering method combined with the sparse coefficients estimation. A method for constructing a suitable monopole dictionary based on the coherence is also proposed so that the convex clustering based method can appropriately estimate distance of the sound sources. Numerical and measurement experiments were performed to investigate the performance of the proposed method.